Analysis of the Italian generic medicines retail market: recommendations to enhance long-term sustainability. (February 2014) - Dylst, Pieter; Vulto, Arnold; Simoens, Steven
<x xml:space="preserve">Abstract</x> Italy is among the European countries with the lowest uptake of generic medicines. This paper provides a perspective on the Italian generic medicines retail market. Fast market entrance of generic medicines in Italy is hindered by several factors: the existence of Complementary Protection Certificates in the past, the large market for copies and multiple cases of patent linkage. Prices of generic medicines in Italy are low compared to other European countries. To contain pharmaceutical expenditure, pharmaceutical companies are currently forced to pay back in case of overspending, which disproportionally penalizes small and fast growing companies, to which most generic companies belong to. Current demand-side policies do not successfully stimulate the use of generic medicines. The current market environment surrounding the Italian generic medicines retail market (i.e., low prices, low volumes) threatens its long-term sustainability. Recommendations to enhance the long-term sustainability of the Italian generic medicines retail market round off this perspective paper.